Experimental studies of long-lifetime cold cathodes for high power microwave oscillators; The 12th IEEE International Pulsed Power Conference, Monterey, CA, june 27-30, 1999; Vol. 2 - Gunin A. V.; Landl V. F.; Korovin S. D.; Mesyats G. A. Gennady Andreyevich; Rostov V. V. (1999, 1999)
В фонде НТБ ТПУ отсутствует